Hình thành điểm dân cư kiểu thành thị ở vùng núi biên giới phía bắc Việt Nam - Trường, Phạm Xuân (Vietnam Journal of Earth Sciences, 2003)
The Formation of urban type's settletements in Northern Mountainy Region of Vietnam